Exile Materialities and Their Brushstrokes of Colour - Rivera, Francisco (Anthropologica)

(untitled) (University of Victoria, 2022)
Urban odonyms and public art that refer to the Chilean dictatorship (1973–1990) are artifacts within the cultural landscapes of Toronto, Laval, and Montreal. As commemorative material devices, I suggest odonyms and public art offer a symbolic way to cope with the experience of exile. Furthermore, these artifacts create social relations between Chilean exiles and Canadian urban spaces that contribute to forming a foreign community and define their present and future. Using a series of photographs, I chronicle the memorialization in Canada of a traumatic period in recent Chilean history.